Executive Functions and Quality of Life in Neurodevelopmental Spectrum. An Outline - Theodoratou, Maria; Gkintoni, Evgenia; Farmakopoulou, Ignatia (Technium Social Sciences Journal, 2023)
Neurocognitive functions play a decisive role in neurodevelopmental disorders affecting the quality of life of individuals with corresponding diagnoses or clinical indications. In addition, the parameter of executives and their subcategories, such as cognitive flexibility, working memory, and inhibition, as well as the possibility of their optimization through special treatment and training, have been extensively studied in the literature over the past several decades. The purpose of this paper is to present the findings of a decade's worth of review studies on executive functions and quality of life in developmental spectrum disorders. Given the genetic heterogeneity and polymorphism of the neurodevelopmental disorder profile and the overlap of outcome parameters, the findings of review studies must be more consistent in explaining causal factors and the efficacy of interventions. Nonetheless, innovative therapeutic approaches and their individualization hold promise for bridging this gap, with the aim of enhancing the quality of life for individuals in this diagnostic category and their close relatives.